Time management practice and associated factors among health professionals working in public and private hospitals in Dessie City, Northeast Ethiopia: a comparative cross-sectional study - Yimer, Ali; Feleke, Amsalu; Yazachew, Lake; Ahmed, Mohammed; Seid, Seada; Adem, Mohammed; Mustofa, Semira Muhidin; Markos, Merkineh; Sirage, Nurye; Kassaw, Abdulaziz Kebede; Mustefa, Nuru Muhammed; Ali, Dawed; et al. (Frontiers in Psychology, 2024)
Background: Time management is a widely ignored concern in all types of organizations, including the healthcare system, despite its crucial role in the achievement of personal and organizational goals. Therefore, determining the practice of time management and its associated factors among health professionals is of paramount importance. Objective: To assess time management practice and associated factors among health professionals working in public and private hospitals of Dessie city, Northeast Ethiopia. Methods: A comparative cross-sectional study was conducted from March 24 -April 24/2021 among 660 health professionals (220 from private hospitals and 440 from public hospitals), who were randomly selected using a stratified sampling technique. Self-administered questionnaire was used to collect data. A multivariable binary logistic regression model was run separately for public and private hospitals. To declare a statistically significant association, a p-value of < 0.05 and a 95% confidence interval were reported. Results: A total of 615 participants responded to the survey and resulted in a response rate of 93.2 %. The magnitude of good time management practice among health professionals in both public and private hospitals was 57.1% (95% CI: 53.5-60.8%). However, the magnitude differed between the public [50.1% (95% CI:45.5-54.7%)] and private hospitals [70.9% (95%CI: 63.5-76.7%)].